Research and modelling of radiobiological effects in the multicellular plant organism by the methods of reliability theory - Yu. A. Kutlakhmedov; I. V. Matveeva; V. A. Groza (Ядерна фізика та енергетика)
Principles of constructing theory of development and establishment of radiobiological reactions in the multilevel hierarchical structures of multicellular organisms are laid down on the bases of mathematical modeling and the theory of biosystems reliability. These principles are consistent with experimental and theoretical studies. Mathematical models were tested on the example of radiobiological effects of the perennial aquatic herbaceous plant Spirodela polyrrhiza. Possibility of using the proposed method for studying radiobiological and biophysical processes for biological structures of various complexity: from cell level to population level of higher plants is justified.